Determination of heavy metal accumulation in ipomoea aquatica using wet destruction method - Mohd Hilmi, Jaafar (2010)
The determination of heavy metals in plants is very important since human intake of toxic trace elements which even at low doses over a long period of time can lead to malfunction of organs and could cause chronic toxicity. Hence, it is necessary to obtain more information on the plants which grow on soils that contain high concentration of heavy metals in order to determine their potential for management of polluted soils and for metal extraction. The objectives of this research are to determine heavy metal (Cr, Ni, Cu, Mn, Cd, Fe, Pb and Zn) uptake by Ipomoea Aquatica cultivated in closed landfill and nursery soil and to compare the concentration of heavy metal in both soil samples besides in order to estimate whether a given soil is suitable for cultivation of plants used as food or feed based on World Health Organization – Maximum Level standard. Acid Digestion Method and Wet Destruction Method were used for digestion process of soils and plants. After dilution, the samples will undergo analysis by using atomic absorption spectrometry (AAS). From result that obtained, the concentrations of all heavy were detected in plant and soil but with various concentrations. There are several heavy metals that exceed the maximum level of WHO standard, Cr (4.16 and 6.92 mg kg-1), Cd (4.67 and 3.93 mg kg-1-1) and Pb (9.66 and 8.87 mg kg). As a conclusion, monitoring of heavy metal distribution data in soil and plant samples are very useful for become main references or guidelines in order to monitoring and avoid environmental pollution become worst in terms of quality of soil and also safety level for vegetables to be consumed.